2003
DOI: 10.1080/08035250310002777
|View full text |Cite
|
Sign up to set email alerts
|

"Maturational lag" hypothesis of attention deficit hyperactivity disorder: an update

Abstract: ADHD is a broad, heterogeneous syndrome and only a subgroup of subjects has a diagnosis of HKD, which is a subset of individuals with severe ADHD combined subtype. Children showing symptoms above the threshold for a diagnosis of ADHD are at risk of developing comorbid conditions and increasing stress in both parents and teachers. In some subjects, ADHD symptoms can improve over time during maturation and development. These children with a diagnosis of ADHD could be viewed as showing variants of normal childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Whether ADHD is a disorder related to a delay in brain maturation or whether it represents a frank derangement of typical development has remained an unsettled question since its earliest descriptions [41]. Several neuroimaging studies have found similarities in functional brain patterns between patients with ADHD and younger TD controls [42], [43]. Interestingly, the NIMH longitudinal study support both types of conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether ADHD is a disorder related to a delay in brain maturation or whether it represents a frank derangement of typical development has remained an unsettled question since its earliest descriptions [41]. Several neuroimaging studies have found similarities in functional brain patterns between patients with ADHD and younger TD controls [42], [43]. Interestingly, the NIMH longitudinal study support both types of conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a cognitive maturation hypothesis suggests that improvement in neurocognition (particularly in executive functioning) during middle childhood and adolescence contributes to ADHD symptom improvements observed during this same time period for some children (Doehnert, Brandeis, Imhof, Drechsler, & Steinhausen, 2010; El-Sayed, Larsson, Persson, Santosh, & Rydelius, 2003; Halperin & Schulz, 2006). Some perspectives suggest that executive function impairments are both the initial cause of symptoms and the mechanism of remittance.…”
mentioning
confidence: 99%
“…However, a more recent study assessing cortical thickness has shown a delay in the maturation of the cortex by approximately 2 years in children with ADHD compared with healthy controls. 11 Also, there is evidence of a lag or delay in cognitive and social development in children with ADHD, 1217 which would suggest regional progressive trajectories differing between children with and without ADHD.…”
mentioning
confidence: 99%